Water quality assessment using IRWQIsc and NSFWQI water quality indicators; A case study: Talar River (Iran) - Mohammad Roshani-Sefidkouhi; Fatemeh Mortezazadeh; Masoumeh Eslamifar; Esmaeil Babanezhad; Masoomeh Sheikhi; Fathollah Gholami-Borujeni (Heliyon)
One of the driest countries in the world, Iran has been facing several challenges related to water shortage, leading to serious social, economic, and environmental impacts. Given the escalating urbanization and industrial development within Iran, a comprehensive assessment of surface water quality utilizing both the US National Sanitation Foundation Water Quality Index (NSFWQI) and the Iran Water Quality Index for surface water (IRWQIsc) is imperative. This study aimed to evaluate the water quality of the Talar River in Mazandaran, Iran, in 2023, through the IRWQIsc and NSFWQI. This study was conducted in the Talar River, located in Mazandaran Province in Iran. Water samples from the Talar River were collected to assess 11 physicochemical parameters from 10 sampling Points. A total of 60 samples were collected monthly during winter and summer 2023. The IRWQIsc and NSFWQI were selected to assess the overall water quality of the Talar River. Nitrate (NO3−) concentrations ranged from 29.32 to 85.89 mg/L across seasons, with average values falling within World Health Organization (WHO) standards. Phosphate (PO43−) and Chemical Oxygen Demand (COD) levels exceeded WHO limits on occasion, while turbidity and electrical conductivity (EC) consistently surpassed both WHO and Environmental Protection Agency (EPA) guidelines. pH and Biochemical Oxygen Demand (BOD) levels remained within acceptable ranges. IRWQIsc and NSFWQI indicated generally poor water quality across all sampling sites, with slight seasonal variations suggesting slightly better conditions in summer for IRWQIsc and winter for NSFWQI. This study indicates that NO3− and PO43− levels meet WHO limits, but COD, turbidity, and EC exceed the recommended threshold. The IRWQIsc and NSFWQI highlight poor conditions resulting from agricultural and industrial pollution. Urgent integrated management is essential to mitigate these impacts and safeguard river health in the face of environmental pressures.